The Capixaba ant species inventory is far from complete: A local scale assessment of the ants (Formicidae) reveals the importance of diversity studies and entomological collections - Ricardo Eduardo Vicente; Jorge Luiz Pereira Souza; Lívia Pires do Prado (Sociobiology, 2023)
The Atlantic Forest is the third largest biome in Brazil, the most sampled, and has the second highest diversity of ant species described. However, these data are spatially very heterogeneous, with the central region of the Atlantic Forest being better sampled. There is a visible gap from the south of Bahia to the north of Rio de Janeiro, comprising the entire state of Espírito Santo. Knowing this biodiversity gap, in this work, we list the ant fauna (Hymenoptera, Formicidae) deposited in the Coleção Entomológica of the Reserva Natural Vale (CERNV), located in the municipality of Linhares, Espírito Santo. The CERNV has 143 ants collected from August 1984, belonging to 63 species, 29 genera, and eight subfamilies. Of the 143 records, 94 are ant workers (66%), 27 queens (19%), and 22 males (15%). Seventy three percent of the ant workers are identified, 52% of queens and 36% of males. The species with the most individuals deposited are Camponotus sp. (15 records), Eciton burchellii (8), Atta sexdens (7), Neoponera villosa (7), and Solenopsis sp. (6). Among the identified ants, 12 species were recorded for the first time in the state of Espírito Santo, Brazil. The collection still holds workers (and probably unidentified males) of a species considered endangered, Dinoponera lucida. We can observe the importance of biological collections for the knowledge of biodiversity, local and regional since species are recorded for the first time in a state whose biome is widely studied, helping to fill in Linnean and Wallacean shortfalls.